Estimation of genetic progress after eight cycles of recurrent selection for common bean grain yield - Silva,Graciele Simoneti da (2010)
The objective of this study was to estimate the genetic progress of eight cycles of recurrent selection for common bean lines with high yield. The base population was obtained from 10 parents differing in several characters. To date, eight selection cycles have been performed. In each cycle the selection process continues after recombination, until lines are established, which are then evaluated more extensively in the experiment of evaluation of elite lines together with lines of other programs. The genetic progress was estimated based on the data of evaluations of these lines in each cycle over the years. The estimated genetic progress of 3.3 % per cycle allows the conclusion that recurrent selection for grain yield is efficient.